Hamstring musculotendon mechanics of prospectively injured elite rugby athletes - Kenneally-Dabrowski, C.; Brown, N. A. T.; Serpell, B. G.; Perriman, D.; Spratford, W.; Sutherland, A.; Pickering, M.; Lai, A. K. M. (Research in Sports Medicine, 2024)
The musculotendon mechanics of the hamstrings during high-speed running are thought to relate to injury but have rarely been examined in the context of prospectively occurring injury. This prospective study describes the hamstring musculotendon mechanics of two elite rugby players who sustained hamstring injuries during on-field running. Athletes undertook biomechanical analyses of high-speed running during a Super Rugby pre-season, prior to sustaining hamstring injuries during the subsequent competition season. The biceps femoris long head muscle experienced the greatest strain of all hamstring muscles during the late swing phase. When expressed relative to force capacity, biceps femoris long head also experienced the greatest musculotendon forces of all hamstring muscles. Musculotendon strain and force may both be key mechanisms for hamstring injury during the late swing phase of running.